Count - Moustafa, Ibrahim (Humanoids, Inc., 2021)
"From Eisner nominated writer/artist Ibrahim Moustafa comes a thrilling sci/fi reimagining of the greatest revenge story ever told, The Count of Monte Cristo! Framed for treason and wrongfully imprisoned at the hands of a jealous rival and a corrupt magistrate, Redxan Samud escapes his hovering prison colony hell-bent on retribution. Given a map from his dying jail companion to the location of a stolen cache of Union Credits large enough to make him wealthy beyond imagination, Samud concocts a plan to exact revenge on those who conspired to let him rot in a cell. Classic literature is given new life in this stunning original graphic novel from a modern master."--Page [4] of cover
Keywords: False imprisonment -- Comic books, strips, etc; Revenge -- Comic books, strips, etc; Gefangener; Rache; Flucht; adventure story comics; Graphic novel adaptations; Comics (Graphic works); Action and adventure comics; Comic; Science fiction comics; Graphic novels